Fiestas : Stories - Bautista, Jacqueline (Book collections on Project MUSE., 2006)
The collection takes the reader into the Civil War and Spain's darkest and most wretched times, and continues through the twentieth century, with stories of ordinary Spaniards living the fiestas of their lives - the loves, deaths, miseries, and minor triumphs of a people determined to make the most of whatever life can throw at them."--Jacket.